(untitled) (RuMoRes, 2009)
The popular participation in the media requires research due the connection of this with the promotion of citizenship. In this case, we present the main characteristics of community radio station, concepts of popular participation, citizenship and present – though preliminary – the configurations of “Jornal FM” radio station. The paper is based on bibliographic research, interviews and non-systematic observation of contents, and aims understand the spaces for the development of citizenship and the kind of popular participation in this radio station. The main results evidences that the community media constitutes a favorable space to popular participation and to the citizenship promotion, however, due to political interests and economic, professional and technological limitations these citizenship spaces become increasingly scarce.